PILAR DAN INFRASTRUKTUR DALAM MENDUKUNG PERKEMBANGAN INDUSTRI HALAL - Arafah, Muh; Jamaluddin (IAIN Ambon, 2024)
The halal industry continues to grow and develop, especially in countries with large Muslim populations, especially in Indonesia. So this article aims to review the pillars and infrastructure that can support the development of the halal industry, especially in Indonesia. This article includes a literature study, namely reviewing literature from various reference sources ranging from books, articles and other scientific works related to the halal industry. The search results show several pillars and infrastructure that can support the development of the halal industry, namely the realization of Halal regulations and certification, the existence of a Halal Certification Institute, the Halal Food and Beverage Industry, Halal Education and Training, Halal Promotion and Marketing, Information Technology and Tracking Systems, Banking and Finance Halal, International Cooperation, finally Halal Tourism Development. Kata Kunci: Industri Halal, Infrastruktur, Pilar, Sertifikasi Halal